Dowodzenie udzielenia dyspensy od przeszkody pokrewieństwa w wyrokach Roty Rzymskiej c. Turnaturi z dnia 25 stycznia 2001 r. i c. De Angelis z dnia 14 lutego 2003 r. - Dzierżon, Ginter (Ius Matrimoniale, 2015)
The author of the presented article focused his attention on the issue of the process of granting a dispensation from the impediment of consanguinity in two verdicts of the Roman Rota – c. Turnaturi of 25th January 2001 and c. De Angelis of 14th February 2003. He proved that the contrary verdicts in the same matter resulted from two different methods of argumentation used by the panel of judges. In the verdict of c. Turnaturi what was taken into consideration was the collected documentation but also other circumstances of the case while in the verdict of c. De Angelis the documents were the main focus of attention. The author believes that in the last sentence the method of decision-making was of positivist nature.